Argumentation-based negotiation for collaborative engineering design. (27th July 2009) - Jin, Yan; Geslin, Mathieu
Designing complex systems requires collaboration among multiple engineers who coordinate to plan tasks, cooperate to resolve dependencies, and co-construct to identify shared objectives and solutions. While collaboration technologies have been developed to date, few can help designers negotiate effectively and reach agreement efficiently. In this paper, we propose an argumentation based engineering negotiation approach that provides a structured framework for designers to specify design situations, compose arguments, and make joint decisions by following various strategies. The details of the proposed approach are described and a case study is presented to demonstrate the effectiveness of the approach.